Barriers to risk reduction: Dontse Yakhe, South Africa. Issue 5 (2nd November 2015) - Harte, Wendy; Sowman, Merle; Hastings, Peter; Childs, Iraphne
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to identify hazard risks and factors impeding the implementation of disaster risk management policies and strategies in Dontse Yakhe in Hout Bay, South Africa. Design/methodology/approach – A case study approach was selected for this research. Interviews were conducted with community leaders and other relevant government and civil society stakeholders. Insights and perceptions of Dontse Yakhe residents were obtained from a focus group interview. Secondary data sources were reviewed and field observations made. Findings – The findings reveal a number of key risks and a complex web of geographical, political, social and environmental factors, and stakeholder interactions, prioritisations and decision making that has created barriers to the implementation of the aims and objectives of disaster risk management policies and strategies in Dontse Yakhe. Originality/value – The contribution of the research is that it provides insight into the complex factors that are stalling development and infrastructure provision, and implementation of risk reduction strategies, in Dontse Yakhe as outlined in disaster risk management policies and strategies, demonstrating a gap between policy rhetoric and practice.